2016
DOI: 10.14507/epaa.24.2391
|View full text |Cite
|
Sign up to set email alerts
|

Measuring, rating, supporting, and strengthening open access scholarly publishing in Brazil

Abstract: This study assesses the extent and nature of open access scholarly publishing in Brazil, one of the world's leaders in providing universal access to its research and scholarship. It utilizes Brazil's Qualis journal evaluation system, along with other relev ant data bases to address the association between scholarly quality and open access in the Brazilian context. Through cross tabulation among these various data sets, it is possible to arrive at a reasonably accurate picture of journals, systems, ratings, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Psychology Journals in Colombia have emerged under the OA model; thus, authors do not pay publication fees -an exception is Revista Latinoamericana de Psicología. Accordingly, the editorial effort has been greater with limited economic resources, a challenge partially solved by devising new tools aimed at decreasing response times (Neto et al, 2016;Piwowar et al, 2018). Research has demonstrated that the OA model has been successful in terms of dissemination and quality, notwithstanding opposition by large publishers who have hegemonically retained and restricted access to content.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychology Journals in Colombia have emerged under the OA model; thus, authors do not pay publication fees -an exception is Revista Latinoamericana de Psicología. Accordingly, the editorial effort has been greater with limited economic resources, a challenge partially solved by devising new tools aimed at decreasing response times (Neto et al, 2016;Piwowar et al, 2018). Research has demonstrated that the OA model has been successful in terms of dissemination and quality, notwithstanding opposition by large publishers who have hegemonically retained and restricted access to content.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that the OA model has been successful in terms of dissemination and quality, notwithstanding opposition by large publishers who have hegemonically retained and restricted access to content. However, editorials with international influence have begun to slowly integrate OA models (Alperin & Rozemblum, 2017;Laakso et al, 2011;Mukherjee, 2009;Neto et al, 2016;Piwowar et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three large-scale corporations (Elsevier, Springer-Kluwer, and Wiley-Blackwell) publish 42% of all articles and control the majority of the most highly prestigious articles in circulation. Another 2000 publishers are responsible for the remaining journals, of which none exceed more than 3% of the total (CARVALHO NETO; WILLINKSKY; ALPERIN, 2016;MCCABE, 2001;MCGUIGAN;RUSSEL, 2008;MILLER;HARRIS, 2004;XIA, 2011) despite the rising criticism regarding access costs and commercial oligopoly (HARO, 2017;MONGEON, 2015a;NOORDEN, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In Latin America, a non-commercial open-access (OA) model, the platinum route (MIGUEL; CHINCHILLA-RODRIGUEZ; MOYA-ANEGÓN, 2011; PACKER, 2011), has been successful due to the government sponsored higher-education system. The most internationally prestigious Brazilian journals are financed by public funds (ALPERIN, 2015;CARVALHO NETO;WILLINSKY;ALPERIN, 2015;MUELLER, 2011;PACKER, 2011;ABADAL, 2014). This is different to the commercial model prevalent in central countries, where publishers privatize research that has been developed with public funds, control access fees and define the number of journals in each research area according to commercial concerns (LARIVIÈRE;…”
Section: Introductionmentioning
confidence: 99%